A study on wastewater treatment sludge utilization in Bulgarian agriculture - Bachev, Hrabrin; Ivanov, Bozhidar (Technology audit and production reserves, 2021)
The issue of sludge utilization from wastewater treatment in agriculture is an important socio-economic and environmental problem in the European Union (EU) and Bulgaria. It is becoming topical issue along with constantly growing amount of produced wastewater treatment sludge, deficiency of lands for their safe disposal, protests of population and interests’ groups, tightening EU restrictions, etc. Furthermore, studies on wastewater treatment sludge utilization are multiplying in relations with their «transformation from wastes into products» and effective inclusion in supply chains and circular economy. Despite their relevance, in-depth studies of the diverse effects and critical factors of wastewater treatment sludge utilization in Bulgarian agri-food chain are at an early stage, mostly focusing on agronomic, economic and/or environmental ones. Thus, the object of research is the effective utilization of sludge from wastewater treatment in Bulgarian agriculture. In the course of the research it is used a qualitative analysis of regulations, and institutional and organizational structure, as well as surveys with managers and experts of urban wastewater treatment plants, and farmers applying and not-using sludge from wastewater treatment in their holdings. As a result of the study, the institutional, political, organizational, personal, educational, informational, social, economic, and environmental factors influencing the utilization of sludge in agriculture in two major regions of the country (Sofia and Burgas) are identified. Impact factors are generally divided into two types: factors influencing the behavior of agents, and factors determining the type and extent of the effects of sludge use in agriculture. In the future, the proposed approach has to be extended and deepen to establish the economic, sectoral and regional specificities on the basis of more representative information from all participants and interested parties in the effective utilization of wastewater treatment sludge.